ANALISIS PELAYANAN PUBLIK BERCIRIKAN GOOD GOVERNANCE PADA BIDANG PELAYANAN PERIZINAN DI DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU DAN KETENAGAKERJAAN KABUPATEN DAIRI - Jadi Pane; Jonson Rajagukguk; Talenta Emma (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Issues plaguing public services include the prevalence of collusion and nepotism (KKN) across central and regional government agencies, sluggish bureaucracy, unfriendly government staff, a lack of information transparency, budgetary waste on matters that do not enhance public welfare, restrictions on freedom of expression, and discriminatory service practices based on ethnicity, religion, social status, or kinship ties. To address these challenges, the government is striving to improve the image of public services by implementing the principles of good governance. It is hoped that applying these principles will maximize service quality and elicit a positive public response, thereby fostering satisfaction and trust in the government. The Investment and Integrated Licensing Agency of Dairi Regency is the government body responsible for handling licensing services for the local community. An assessment of good governance at the agency reveals that these principles have not yet been fully implemented; issues persist regarding the timeliness of administrative processing, discriminatory treatment of the public, the prioritization of kinship ties, and a lack of responsiveness among staff. Four specific principles have not been optimally applied: excellent service, democracy and participation, effectiveness and efficiency, and fairness. This study aims to examine the extent to which good governance principles have been effectively implemented. It employs a qualitative approach to understand the situation and provide an explanatory overview of the issues facing the Dairi Regency Investment and Integrated Licensing Agency. The study utilizes both key and primary informants, with data collected through interviews and document analysis. Data analysis involves the stages of data reduction, data presentation, and conclusion drawing.